Rhodium‐Catalyzed Cross‐Cyclotrimerization and Dimerization of Allenes with Alkynes. Issue 23 (25th April 2016) - Sakashita, Kazuki; Shibata, Yu; Tanaka, Ken
Abstract: It has been established that a cationic rhodium(I)/binap complex catalyzes the cross‐cyclotrimerization of two molecules of a monosubstituted allene with one molecule of a functionalized alkyne to give 3, 6‐dialkylidenecyclohex‐1‐enes. In contrast, the reactions involving di‐ or trisubstituted allenes and/or unfunctionalized alkynes afforded cross‐dimerization products, substituted dendralenes, through β‐hydrogen elimination from the corresponding rhodacycles. Abstract : A triple cross : A cationic rhodium(I)/binap complex catalyzes the cross‐cyclotrimerization of two molecules of a monosubstituted allene with one molecule of a functionalized alkyne to give 3, 6‐dialkylidenecyclohex‐1‐enes. In contrast, the reactions involving di‐ or trisubstituted allenes and/or unfunctionalized alkynes afforded cross‐dimerization products, substituted dendralenes. binap=2, 2′‐bis(diphenylphosphino)‐1, 1′‐binaphthyl.